The Effect of Work Discipline and Work Motivation on Employee Performance Cleaning Service at PT Ganendra Wijaya - Sefhia Abi Jelita; Dwi Gema Soegesti (Journal of Research in Social Science and Humanities, 2025)
The purpose of this study was to analyze the effect of work discipline and work motivation on the performance of cleaning service employees at PT Ganendra Wijaya. This study used a quantitative method, with a population of all employees of PT Ganendra Wijaya in Lampung Province totaling 148 people. The sampling technique used was saturated sampling, where all members of the population were used as respondents in this study. Data collected through observation and questionnaires were analyzed using validity tests, reliability tests, multiple linear regression analysis, and hypothesis tests. The results of the validity test showed that all statement items were declared valid, while the reliability test indicated that all variables had reliable properties. Multiple linear regression analysis showed that work discipline (X1) had a positive effect on employee performance (Y) with a regression coefficient of 0.658, while work motivation (X2) also had a positive effect with a coefficient of 0.305. The coefficient of determination test (R2) revealed that 85.2% of the variation in employee performance could be explained by work discipline and work motivation. the results of the hypothesis test show that both work discipline and work motivation have a significant influence on employee performance, with a significant value of 0.001. This study emphasizes the importance of work discipline and work motivation in improving employee performance at PT Ganendra Wijaya.